Abdominoplasty as the patient impetus for selection of the deep inferior epigastric artery perforator free flap for knee coverage. Issue 2 (1st August 2013) - Hallock, Geoffrey G.
<x xml:space="preserve">Abstract</x> Extensive wounds about the knee can rarely be covered with local or even regional flaps. Free flaps often then become obligatory. Many factors will determine the surgeon's selection of the best donor site. Yet the patients' concerns with donor site morbidity cannot be overlooked. Most would agree that a large, but relatively thin flap would be optimal to preserve knee mobility. The deep inferior epigastric artery perforator (DIEAP) flap would therefore not usually be the donor site of choice from the surgeon's perspective. However, the opportunity to have a concomitant abdominoplasty that would improve body image or result in a scar readily hidden by clothing is an enticement for the patient not to be dismissed, under what normally are otherwise depressing circumstances. Over the past decade, three female patients have chosen the DIEAP free flap solely for the latter reasons, fully realizing that later flap revision would be needed to improve the function and appearance at the recipient site. © 2013 Wiley Periodicals, Inc. Microsurgery 34:102–105, 2014.